Modelization of a water tank including a PCM module - Ibáñez, Manuel; Cabeza, Luisa F.; Solé, Cristian; Roca, Joan; Nogués, Miquel (Applied thermal engineering, 2006)
The reduction of CO 2 emissions is a key component for today’s governments. Therefore, implementation of more and more systems with renewable energies is necessary. Solar systems for single family houses or residential buildings need a big water tank that many times is not easy to locate. This paper studies the modelization of a new technology where PCM modules are implemented in domestic hot water tanks to reduce their size without reducing the energy stored. A new TRNSYS component, based in the already existing TYPE 60, was developed, called TYPE 60PCM. After tuning the new component with experimental results, two more experiences were developed to validate the simulation of a water tank with two cylindrical PCM modules using type 60PCM, the cooldown and reheating experiments. Concordance between experimental and simulated data was very good. Since the new TRNSYS component was developed to simulate full solar systems, comparison of experimental results from a pilot plant solar system with simulations were performed, and they confirmed that the type 60PCM is a powerful tool to evaluate the performance of PCM modules in water tanks.